Antigen Gene Transfer to Human Plasmacytoid Dendritic Cells Using Recombinant Adenovirus and Vaccinia Virus Vectors - Hetty J. Bontkes; Janneke J. Ruizendaal; Marco W. J. Schreurs; Duco Kramer; Chris J. L. M. Meijer; Erik Hooijberg (Cellular Oncology)
Recombinant adenoviruses (RAd) and recombinant vaccinia viruses (RVV) expressing tumour-associated antigens (TAA) are used as anti-tumour vaccines. It is important that these vaccines deliver the TAA to dendritic cells (DC) for the induction of a strong immune response. Infection of myeloid DC (MDC) with RAd alone is relatively inefficient but CD40 retargeting significantly increases transduction efficiency and DC maturation. Infection with RVV is efficient without DC maturation. Plasmacytoid dendritic cells (PDC) play a role in the innate immune response to viral infections through the secretion of IFNα but may also play a role in specific T-cell induction. The aim of our study was to investigate whether PDC are better targets for RAd and RVV based vaccines. RAd alone hardly infected PDC (2%) while CD40 retargeting did not improve transduction efficiency, but it did increase PDC maturation (25% CD83 positive cells). Accordingly, specific CTL activation by RAd infected PDC was limited (the number of IFNγ producing CTL was reduced by 75% compared to stimulation with peptide loaded PDC). RVV infected PDC specifically stimulated CTL but PDC were not activated. These Results indicate that PDC are not ideal targets for RAd and RVV based vaccines. However, PDC induced specific CTL activation after pulsing with recombinant protein, indicating that PDC can also cross-present antigens released from surrounding infected cells.